Umur Lelah Hasil Cetak Injeksi Bahan Campuran Daur Ulang dari Polipropilin dan High Impact Polystyrene - Syamsul Hadi; Daffa Aureza Andhika; Ivan Rosdinata; Dhea Septa Ristiana; Khoirul Anam; Zakijah Irfin (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Waste from used Polypropylene (PP) and High Impact Polystyrene (HIPS) plastic is problematic in its management. The purpose of this research is to obtain the fatigue life of a mixture of used PP and HIPS plastics in its pure plastic. The research method is through the stages of mixing pure PP and 50% volume of used PP, pure HIPS and 50% volume of used HIPS, injection molding of R.R. Moore standard fatigue test specimens for pure PP, pure HIPS, pure PP + used PP, and pure HIPS + used HIPS, checking the straightness and smoothness of the molded specimen surface, fatigue testing with increasing serial loads, analysis of the bending stress curve (S) against fatigue life (N). The results showed that mixing used PP and used HIPS in pure plastic affected the fatigue life at the test speed (n)=2100 rpm for recycled PP was 9.84% shorter than pure PP, and at n=1600 rpm for recycled PP it was 9.32% shorter than pure PP, while at n=2100 rpm for recycled HIPS it was 4.45% shorter than pure HIPS, and at n=1600 rpm for recycled HIPS is 4.77% shorter than pure HIPS, while the fatigue life of pure PP is 1627704 cycles and the fatigue life of pure HIPS is 1291636 cycles or the fatigue life of pure HIPS is 20.65% shorter than pure PP, the implication of which is that the addition of used PP and used HIPS reduces the fatigue life to 9.84% for PP and 4.45% for HIPS.